Considerations on Sustainability on the Romanian Fruit Market – Production and Consumption Trends - Gabriel POPESCU; Marian Catalin CUCU; Ioana PANAIT (Communications of International Proceedings, 2020)
Fruits are foods with many human health benefits and since ancient times they have been a major source of energy with low-calorie content. For agriculture, fruit plantations represent a very important category due to the high incomes generated per hectare. The present paper aims to analyse the Romanian fruit market, both in terms of demand and in terms of supply, identifying the consumption trends of the population and those of supply. The research results reflect the current situation, as well as the evolution of the Romanian fruit market in terms of quantity consumed, market value, quantities produced, import and export.
Keywords: Sustainable Development; Organic Fruits; Fruits Processing; Fruits Supply Chain.